The Unsinkable Fantasy - Geneviève Morel (EJP import test, 2022)
Summary: It is because the symptom is a source of complaint that one speaks about it in psychoanalysis, to get rid of it. However, fantasy is so sweet / pleasurable that there is no incentive to speak of it, as Freud noted. We would rather keep to ourselves this intimate and painless satisfaction. Yet without addressing the fantasy, there is no hope that symptoms will give way, even if they appear to move / shift / transform themselves. But the fantasy is not deciphered, even though one may speak of the symptoms that are built on it. What to do then? We will study, based on clinical and literary examples, how Lacan reversed the Freudian problematic by theorizing psychoanalysis as a staging of fantasy. One possible outcome of the cure could therefore see the fantasy losing its substance, and the symptom reducing itself around what remains of it.
Keywords: fantasy; jouissance; Lacan; punishment; Transformation of Symptom